Prevalence of HIV Infection Among Tuberculosis Patients in Sindh, Pakistan (Medical Forum Monthly, 2024)
Objective: To determine the occurrence of HIV infection among tuberculosis patients in Sindh, Pakistan.Study Design: A cross sectional record analysis study.Place and Duration of Study: This study was conducted at the department of Pulmonology and department of Biochemistry Ghulam Muhammad Mahar Medical College, Sukkur covering the period from January 2014 to October,2018.Materials and Methods: Diagnosis of TB was performed by AFB smear and X-ray chest. For the screening of HIV, Chromatographic test was performed and for substantiation of HIV ELISA technique were used.Results: Overall 3410 TB patients were analyzed and 13.9% HIV positive were detected. Of these 3410 patients, 39% had pulmonary Tuberculosis and 42% had extra pulmonary Tuberculosis (EPTB).Conclusion: The commonness of HIV- Tuberculosis co-infection was 13.9%. Both male and female patients were affected.